2020
DOI: 10.1186/s13002-020-00368-2
|View full text |Cite
|
Sign up to set email alerts
|

Domestication of aromatic medicinal plants in Mexico: Agastache (Lamiaceae)—an ethnobotanical, morpho-physiological, and phytochemical analysis

Abstract: Background Most reports of domesticated plants that involve a domestication gradient or inter-specific hybridization in Mexico have focused on those used as food. This study provides knowledge about these processes in two aromatic medicinal plants, Agastache mexicana (Lamiaceae) and A. m. subsp. xolocotziana, widely used in Mexican traditional medicine for the treatment of gastrointestinal ailments and for their sedative effect. Different populations of A. mexicana along a gradient of domestication are found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
3
13
0
4
Order By: Relevance
“…Our research concurs with others made on aromatic plants that found differences in the chemical composition of managed individuals compared to wild individuals, based on their utilitarian attributes [10,97], which can augment the desired phenotypes and even eliminate non-desired phenotypes [5].…”
Section: Organic Compounds In Copal Resin and Their Potential Associasupporting
confidence: 91%
See 2 more Smart Citations
“…Our research concurs with others made on aromatic plants that found differences in the chemical composition of managed individuals compared to wild individuals, based on their utilitarian attributes [10,97], which can augment the desired phenotypes and even eliminate non-desired phenotypes [5].…”
Section: Organic Compounds In Copal Resin and Their Potential Associasupporting
confidence: 91%
“…These processes could be a result of the selection of attributes that are desirable in this resource, as suggested by Carrillo-Galván et al [10] and Bautista et al [7], who found that human selection may be generating changes in the chemical pro le of secondary metabolites.…”
Section: Organic Compounds In Copal Resin and Their Potential Associamentioning
confidence: 99%
See 1 more Smart Citation
“…The latter may mean that management is modifying the abundance of organic compounds that give copal its scent. These processes could be a result of the selection of attributes that are desirable in this resource, as suggested by Carrillo-Galván et al [10] and Bautista et al [7], who found that human selection may be generating changes in the chemical profile of secondary metabolites.…”
Section: Organic Compounds In Copal Resin and Their Potential Associamentioning
confidence: 99%
“…Mesoamerica is the cultural region comprised from southern Mexico to northern Costa Rica [1], which has contributed to humanity through important crops, plant management strategies, and plant diversification through domestication [2][3][4]. The agricultural and silvicultural management of plant populations have promoted morphological, physiological, genetic, and phytochemical diversification in features of human interest [5][6][7][8][9][10], compared with unmanaged or incipiently managed populations [11]. Silvicultural management, also referred to as in situ management, can include the collection, tolerance, promotion, and protection of some individuals with desirable attributes in wild vegetation, agroforestry systems, fallow areas, and other anthropized zones [4,5,8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%